Anisotropic microparticles for differential drug release in nerve block anesthesia. Issue 8 (22nd January 2021) - B. S, Shivakumar; Gopalakrishnan-Prema, Vignesh; Raju, Gayathri; Mathew, Sumi E.; Katiyar, Neeraj; Menon, Deepthy; Shankarappa, Sahadev A.
Abstract : Stretch-induced anisotropy in bupivacaine-loaded PLGA micro particles (BMPs) induced stronger nerve blocks compared to spherical particles. Abstract : Microparticle shape, as a tunable design parameter, holds much promise for controlling drug-release kinetics from polymeric microparticulate systems. In this study we hypothesized that the intensity and duration of a local nerve block can be controlled by administration of bupivacaine-loaded stretch-induced anisotropic poly(lactic- co -glycolic acid) microparticles (MPs). MPs of size 27.3 ± 8.5 μm were synthesized by single emulsion method and subjected to controlled stretching force. The aspect ratio of the anisotropic–bupivacaine MPs was quantified, and bupivacaine release was measured in vitro . The anisotropic MPs were administered as local nerve block injections in rats, and the intensity and duration of local anesthesia was measured. Bupivacaine-loaded anisotropic MPs used in this study were ellipsoid in shape and exhibited increased surface pores in comparison to spherical MPs. Anisotropic MPs exhibited a higher rate of bupivacaine release in vitro, and showed significantly ( P < 0.05) stronger sensory nerve blocking as compared to spherical bupivacaine MPs, even though the duration of the nerve block remained similar. This study demonstrates the utility of stretch-induced anisotropic MPs in controlling drug release profiles from polymeric MPs, under both in vitro and in vivo conditions. We show that shape, as a tunable design parameter, could play an important role in engineering drug-delivery systems.